Evaluation of Effective Morphophysiological Characteristics on Grain Yield of Barley Under Salinity Stress Conditions - Zare-Kohan, Mahdiyeh; Jelodar, Nadali Babaeian; Tabatabaee, Seyed Ali; Nezhad-raeini, Mohammadreza Ghasemi (Journal of Research (Science), 2025)
Salinity stress is one of the most important abiotic stresses, especially in arid and semi-arid regions. The current research was performed to identify traits associated with barley yield under normal and salinity stress conditions. In this research, 150 barley cultivars were planted in alpha lattice design with five incomplete blocks in two replications at non-stress and salinity stress (EC=12 dsm-1) conditions at Agriculture and Natural Resources Research and Education Center, Yazd, Iran. Correlation analysis showed that the biological yield and harvest index had the highest significant positive correlation with grain yield in experimental environments. The result of stepwise regression indicated that biological yield, harvest index, relative water content, leaf chlorophyll content, thousand-grain weight, and flag leaf length were the most important influential traits under normal conditions that explained 97.93% of the total variance of grain yield. While biological yield, harvest index, days to tillering, grain filling period, and days from stemming to heading entered in the model under salinity stress, which explained 97.46% of the total variance. According to the path analysis results, the biological yield and harvest index had the most direct and positive effect on grain yield in non-stress and salinity stress conditions. The factor analysis determined seven factors for non-stress and eight factors for salinity stress conditions that explained 75.2 and 80.5% of the data's total variance. Overall, this study showed that biological yield and harvest index were the main traits related to grain yield that can be used in barley breeding programs in selecting high-yielding cultivars and lines.